Value addition in sesame: A perspective on bioactive components for enhancing utility and profitability - Pathak, Niti; Rai, A.K.; Kumari, Ratna; Bhat, K.V. (Pharmacognosy Reviews)
Sesame seed is a reservoir of nutritional components with numerous beneficial effects along with health promotion in humans. The bioactive components present in the seed include vital minerals, vitamins, phytosterols, polyunsaturated fatty acids, tocopherols and unique class of lignans such as sesamin and sesamolin. The presence of phenylpropanoid compounds namely lignans along with tocopherols and phytosterols provide defense mechanism against reactive oxygen species and increases keeping quality of oil by preventing oxidative rancidity. In this article, we have reviewed the nutraceutical, pharmacological, traditional and industrial value of sesame seeds with respect to bioactive components that hold high antioxidant value. Valuable information on superior functional components of sesame will strongly promote the use of sesame seeds in the daily diet world‑wide. In spite of huge repertoire of sesame germplasm collection, limited research efforts on the use of conventional and biotechnological methodologies have resulted in minimal success in developing nutritionally superior cultivars. In consequence, value addition efforts in sesame would enable development of genotypes with high antioxidant activity and subsequently prevention of free radical related diseases. Modification of bioactive components in sesame would enable production of stabilized sesame oil with enhanced shelf life and better market value.
Keywords: Bioactive components; lignans; nutraceuticals; phytosterols; tocopherols